The Experience of Symbolic Violence among Deaf Students in Disability-Friendly Universities: A Pierre Bourdieu Perspective - Nathacha Nathacha; Moh. Mudzakkir; Wardatul Adawiah; Eufrasia Kartika Hanindraputri (SOCIUS, 2026)
This research is driven by the contradictory phenomenon at University X, where its status as a "Disability-Friendly Campus" conceals underlying practices of marginalization within daily interactions. The study aims to analyze the mechanisms of euphemization, censorization, and misrecognition in perpetuating the dominance of hearing culture within an inclusive higher education setting. Adopting a qualitative approach with a phenomenological design, data were collected through observations and in-depth interviews via WhatsApp text messages with 10 deaf students. Participants were selected using snowball. The data were analyzed interactively—including reduction, display, and verification—and sharpened using Pierre Bourdieu's theory of symbolic violence. This theory assumes that power dominance operates subtly through the internalization of dominant group values, which are perceived as natural or taken for granted (doxa) by the dominated group. The results indicate that the claim of inclusivity at University X remains confined to the physical dimension, while symbolic violence persists through: (1) euphemization in the form of "special" treatment that paralyzes agency; (2) censorization through inaccessible auditory communication structures; and (3) misrecognition, where students internalize systemic barriers as personal failures. The novelty of this study lies in its application of the symbolic violence perspective to examine the gap between idealized policies and the social realities experienced by deaf students, which are often overlooked in conventional studies focusing primarily on physical accessibility.